Josip Leović : (1885.-1963.) : osječki slikar, grafičar i kipar - Zec, Daniel (Osijek : Galerija likovnih umjetnosti, 2013)
Summary
Bibliografija. - Kazalo
Keywords: Leović, Josip (1885-1963) -- slikar -- grafičar -- kipar